2011
DOI: 10.1673/031.011.10101
|View full text |Cite
|
Sign up to set email alerts
|

Host Specificity and Temporal and Seasonal Shifts in Host Preference of a Web-Spider ParasitoidZatypota percontatoria

Abstract: Current knowledge about polysphinctine parasite wasps' interactions with their spider hosts is very fragmented and incomplete. This study presents the host specificity of Zatypota percontatoria (Müller) (Hymenoptera: Ichneumonidae) and its adaptation to varying host availability. Two years of field observations show that Z. percontatoria is a stenophagous parasitoid that parasitizes only five closely related web-building spiders of the family Theridiidae (Araneae). Within the Theridiidae it attacks only specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 27 publications
1
21
1
1
Order By: Relevance
“…Similar interspecific differences were shown in other host–parasite interactions, including amphipod–acanthocephalan (Tain et al ., ), spider–parasitoid wasps (Eberhard, ; Korenko & Pekár, ) and other ant–slavemaker systems (Bauer et al ., ). In some cases, parasites readily switch between host species, preferentially targeting the most abundant host (Korenko et al ., ), whereas in others, host preference reflects differences in the ability of parasites to manipulate host behaviour (Tain et al ., ). In our study system, parasite prevalence is higher in T. longispinosus populations, even in communities where T. curvispinosus is more abundant (Brandt & Foitzik, ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar interspecific differences were shown in other host–parasite interactions, including amphipod–acanthocephalan (Tain et al ., ), spider–parasitoid wasps (Eberhard, ; Korenko & Pekár, ) and other ant–slavemaker systems (Bauer et al ., ). In some cases, parasites readily switch between host species, preferentially targeting the most abundant host (Korenko et al ., ), whereas in others, host preference reflects differences in the ability of parasites to manipulate host behaviour (Tain et al ., ). In our study system, parasite prevalence is higher in T. longispinosus populations, even in communities where T. curvispinosus is more abundant (Brandt & Foitzik, ).…”
Section: Discussionmentioning
confidence: 99%
“…percontatoria and their theridiid host have been studied by Korenko et al . () and Korenko and Pekár (). In these studies, the average prevalence of parasitism in Central Europe was observed to be 1.74–0.83%.…”
Section: Introductionmentioning
confidence: 97%
“…pinastri L. Koch, 1872, Phylloneta impressa (L. Koch, 1881), Neottiura bimaculata (Linnaeus, 1767), Platnickina tincta (Walckenaer, 1802), Heterotheridion nigrovariegatum (Simon, 1873) and Paidiscura pallens (Blackwall, 1834) (Korenko et al . ). Interactions between Z .…”
Section: Introductionmentioning
confidence: 97%
“…Many species of spider are parasitized by a variety of insects (Eason et al 1967), most of which belong to the arthropod orders Hymenoptera and Diptera (Korenko et al 2011), as well as some nematodes (Poinar 1985(Poinar , 1987Penney & Bennett 2006), and kleptoparasitic spiders (Hénaut et al 2005). Considering only dipteran parasitoids, those in the family Acroceridae are the most representative (Schlinger 1993), although some species from the Tachinidae, Chloropidae, and Drosophilidae families also parasitize spiders (Eason et al 1967;Disney 1994).…”
mentioning
confidence: 99%